The Effect of Covid-19 on the Performance of the JSE-TOP40 Listed Companies - Mosimanyane, Lethabo; Marozva, Godfrey (Acta Universitatis Danubius. Œconomica, 2024)
In this article, the effect of covid-19 pandemic on the performance of TOP40-JSE listed companies is investigated using the two-step difference generalised method of moments (GMM) approach. JSE-Top40 listed companies’ data from 24 November 2020 to 29 July 2022 was used to examine the relationship. This is motivated by desire to understand how future pandemic could be managed and thus help contribute to measures that could minimise the adverse effect of the pandemic. Results showed that the Covid-19 as proxied by number of new deaths positively impacted the stock return of the selected companies. The JSE-TOP40 companies offered investors a safety net during the period of a pandemic. The results show that companies were able to change their business models and strategies to counter the effects of a pandemic.